Effects of supervised exercise training during pregnancy on psychological well-being among overweight and obese women: secondary analyses of the ETIP-trial, a randomised controlled trial - Garnæs, Kirsti Krohn (BMJ Open, 2019)
OBJECTIVES: Women with high body mass index (BMI) have increased risk for symptoms of anxiety and depression during pregnancy and postpartum. In this prespecified secondary analysis from the exercise training in pregnancy trial, our aim was to examine effects of supervised exercise during pregnancy on psychological well-being in late pregnancy and postpartum among women with a prepregnancy BMI ≥28 kg/m(2). DESIGN: Single-centre, parallel group, randomised controlled trial. SETTING: University Hospital, Norway. PARTICIPANTS: Ninety-one women (age 31.2±4.1 years, BMI 34.5±4.2 kg/m(2)), 46 in the exercise group, 45 in the control group, were included in the trial. INTERVENTION: The exercise group was offered 3 weekly supervised exercise sessions (35 min of moderate intensity walking/running and 25 min of resistance training), until delivery. PRIMARY AND SECONDARY OUTCOMES MEASURES: Primary analyses were based on intention to treat, with secondary perprotocol analyses. To assess psychological well-being, we used the ‘Psychological General Well-Being Index’ (PGWBI) at inclusion (gestational week 12–18), late pregnancy (gestational week 34–37) and 3 months postpartum. We assessed postpartum depression using the ‘Edinburgh Postnatal Depression Scale’ (EPDS). RESULTS: Numbers completed data collection: late pregnancy 72 (exercise 38, control 36), postpartum 70 (exercise 36, control 34). In the exercise group, 50% adhered to the exercise protocol. Baseline PGWBI for all women was 76.4±12.6. Late pregnancy PGWBI; exercise 76.6 (95% CI 72.2 to 81.0), control 74.0 (95% CI 69.4 to 78.5) (p=0.42). Postpartum PGWBI; exercise 85.4 (95% CI 81.9 to 88.8), control 84.6 (95% CI 80.8 to 88.4) (with no between-group difference, p=0.77). There was no between-group difference in EPDS; exercise 2.96 (95% CI 1.7 to 4.2), control 3.48 (95% CI 2.3 to 4.7) (p=0.55). CONCLUSIONS: We found no effect of supervised exercise during pregnancy on psychological well-being among women with high BMI. Our findings may be hampered by low adherence to the exercise protocol. TRIAL REGISTRATION NUMBER: NCT01243554